Sano, normale o malato - Del Missier, Giovanni (Il sogno della farfalla, 2019)
This article analyzes the concepts of illness, health and normality with the aim of highlighting how the last two terms cannot be considered as synonymous when referring to body medicine and even more when applied to psychology and psychiatry. On the other hand, in the specific case of children deaths due to parents’ abandonment, a striking contradiction results between the pathological abnormality that determines these events and at the same time the judgment of the responsible parent as normal individuals. In the light of a psychotherapeutic methodology founded on the non-conscious human thought dimension and on the Human Birth Theory, the author analyzes clinical cases in order to propose an etiological hypothesis. This can allow not only to establish a correct psychopathological diagnosis and an adequate therapy but in particular an attempt of research on a possible although difficult form of prevention.